2014
DOI: 10.1590/s1519-99402014000300021
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade do mel de Apis mellifera L. relacionadas às boas práticas apícolas

Abstract: Rev. Bras. Saúde Prod. Anim., Salvador, v.15, n.3, p.731-739 jul./set., 2014 http://www.rbspa.ufba.br ISSN 1519 9940 731 Qualidade do mel de Apis mellifera L. relacionadas às boas práticas apícolasHoney quality from "Apis mellifera" L. related to good apicultural practices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
3
8
0
4
Order By: Relevance
“…Moreover, these values have be shown to be superior when compared to the average values of aw of 0.58 to 0.60 found by Moura et al (2014) that evaluated honeys in the semi arid region of Piauí; to the values of 0.49 to 0.66 in honeys from São Paulo (Denardi et al, 2005); to the Schalabitz et al (2010) that described values between 0.54 to 0.62 in the region of Taquari Valley, in the State of Rio Grande do Sul; aw of 0.55 Moroccan honeys (Malika et al, 2005), and of Kacaniová et al (2007), that found values between 0.46 to 0.66 in honeys from Slovakia.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Moreover, these values have be shown to be superior when compared to the average values of aw of 0.58 to 0.60 found by Moura et al (2014) that evaluated honeys in the semi arid region of Piauí; to the values of 0.49 to 0.66 in honeys from São Paulo (Denardi et al, 2005); to the Schalabitz et al (2010) that described values between 0.54 to 0.62 in the region of Taquari Valley, in the State of Rio Grande do Sul; aw of 0.55 Moroccan honeys (Malika et al, 2005), and of Kacaniová et al (2007), that found values between 0.46 to 0.66 in honeys from Slovakia.…”
Section: Resultsmentioning
confidence: 71%
“…The use of the EUBP favors the security of the product when essential cares are taken in order to obtain a good quality honey. To do this, the EUBP and the implantation of Best Practices for Beekeeping (BPB) result in a quality improvement of the honey produced in the State and this necessity appeared with the arousing of exportations and the demands from the foreign market (Vilela, 2000;Moura et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…O mel é um produto considerado de acidez moderada e está relacionada com a origem botânica do néctar e pelas condições do pH do solo (MOURA et al, 2014). Os estudos realizados por SOHAIMY et al, (2015) com amostras de mel de diferentes regiões do Oriente, registraram valores de pH que variaram de 4,11 (±0,02) a 4,63 (±0,03) para as amostras analisadas.…”
Section: Resultados E Discussõesunclassified
“…Além do investimento local e organização dos produtores para a produção do mel, é relevante destacar a aptidão apícola de cada região. O uso da terra e atividades no entorno dos locais de instalação do apiário são fatores que podem comprometer a quantidade e qualidade do mel produzido (WOLFF et al, 2006;MOURA et al, 2014;DAMASIA-GOMES et al, 2015). Dentre os municípios goianos, muitos apresentam intensa atividade agrícola com culturas temporárias e alto impacto sobre os recursos naturais, sendo que poucos apresentam atividades sustentáveis alternativas com menor impacto sobre os recursos naturais.…”
Section: Resultsunclassified